Metallic porous micro-nano composite wicking core and preparation method thereof
Patent Information
- Application Number
- CN202510669185.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-23
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2045-05-23
AI Technical Summary
[0004]由热管作用原理可知,当多孔吸液芯孔径减小时,多孔吸液芯热管的毛细力升高,渗透率降低;而当多孔吸液芯孔径增大时,多孔吸液芯热管的毛细力降低,渗透率升高;也就是说,普通单一孔结构多孔芯热管的多孔吸液芯存在毛细力和渗透性此消彼长的对立关系,这一关系使普通单一孔结构多孔芯热管的传热能力受到限制
[0019] 1. This invention obtains a metal porous micro-nano composite liquid wick by setting micro-protrusion structures on the surface of a porous metal substrate and setting nano-porous structures on the micro-protrusion structures. The micro-nano structures effectively increase the surface area of the composite liquid wick, making it have higher heat transfer efficiency and stability compared to a single-pore unit liquid wick.
Smart Images

Figure CN120467069B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of micro-nano fabrication technology of porous metal materials, specifically relating to a porous metal micro-nano composite liquid absorbent core and its preparation method. Background Technology
[0002] In recent years, with the rapid advancement of science and technology, optoelectronic technologies have developed rapidly, and electronic components are becoming increasingly miniaturized, high-power, and highly integrated. Solving the problem of heat dissipation under high heat flux density in confined spaces remains a serious challenge. Heat pipes, as highly efficient heat transfer elements, possess advantages such as high thermal conductivity, good temperature uniformity, and high reliability, and have been widely used in smart devices, aerospace, and other fields.
[0003] When a heat pipe is working, it absorbs heat by vaporizing the working fluid, then releases heat by liquefying it at the cold source. Simultaneously, capillary force provided by the porous wick drives the working fluid back to the evaporation section of the heat pipe, ensuring that the working fluid absorbs heat again and vaporizes, thus achieving cyclic heat dissipation. The porous metal wick, as a crucial component of the heat pipe, not only provides a channel for the flow of the working fluid but also generates capillary force to drive its return to the evaporation section. Therefore, the structure of the porous metal wick directly affects the heat transfer performance of the heat pipe.
[0004] As the working principle of heat pipes shows, when the pore size of the porous wick decreases, the capillary force of the heat pipe increases and the permeability decreases; conversely, when the pore size increases, the capillary force decreases and the permeability increases. In other words, a conventional single-pore porous wick heat pipe exhibits an inverse relationship between capillary force and permeability, which limits its heat transfer capacity. Therefore, it is necessary to consider the characteristics of each part of the heat pipe and construct a metal porous micro / nano composite wick to balance the contradiction between capillary force and permeability, thereby improving the heat transfer capacity of the heat pipe. Summary of the Invention
[0005] The technical problem to be solved by this invention is to address the shortcomings of the prior art by providing a metal porous micro / nano composite liquid-absorbing core. This metal porous micro / nano composite liquid-absorbing core increases the surface area by setting micro-protrusion structures on the surface of a metal porous substrate and then setting nanoporous structures on these micro-protrusion structures. This results in a combination of good capillary suction force and permeability for liquid working fluids, resolving the contradiction between the inverse relationship between capillary force and permeability in porous liquid-absorbing cores.
[0006] To solve the above-mentioned technical problems, the technical solution adopted by the present invention is as follows: a metal porous micro-nano composite liquid absorption core, characterized in that it includes a metal porous substrate, a micro-protrusion structure disposed on the surface of the metal porous substrate, and a nanoporous structure on the micro-protrusion structure, wherein the porosity of the metal porous substrate is 15% to 45%, the maximum pore size is 5 μm to 25 μm, and the thickness is 1 mm to 10 mm; the height of the micro-protrusion structure is 0.1 mm to 0.5 mm, the length is 0.3 mm to 0.7 mm, and the width is 0.3 mm to 0.7 mm; the nanoporous structure is prepared by anodizing process, and the thickness is 5 μm to 30 μm, and the pore size is 30 nm to 95 nm.
[0007] Meanwhile, this invention also discloses a method for preparing the above-described porous metal micro / nano composite liquid-absorbing core, the method comprising the following steps:
[0008] Step 1: Pressing and forming of porous metal matrix: After loading the metal powder into the mold, it is placed in a cold isostatic pressing equipment for cold isostatic pressing and forming to obtain a green metal porous matrix; the pressure of the cold isostatic pressing is 160MPa~200MPa, and the holding time is 20s~30s.
[0009] Step 2: Sintering of the porous metal matrix: The porous metal matrix green body obtained in Step 1 is sintered to obtain a porous metal matrix; the sintering temperature is 950℃~1250℃, and the holding time is 1.5h~3.5h.
[0010] Step 3: Machining of the micro-boob structure: The machining model of the micro-boob structure is designed using CAXA software. Then, the porous metal substrate obtained in Step 2 is micro-milled using the designed machining model to form the micro-boob structure, resulting in a porous metal substrate with a micro-boob structure on its surface. The feed rate used in the micro-milling is 0.01mm to 0.02mm, and the rotation speed is 8000rpm to 12000rpm.
[0011] Step 4: Surface nanostructuring of the micro-protrusion structure: The porous metal substrate with micro-protrusion structure obtained in Step 3 is placed as the anode in an electrolytic cell containing ethylene glycol electrolyte, and a platinum sheet is used as the cathode for anodic oxidation treatment to form a nanoporous structure on the micro-protrusion structure, resulting in a porous metal micro / nano composite liquid absorbent core blank; the ethylene glycol electrolyte contains 0.25%–1.25% ammonium fluoride by mass and 1%–2% H2O by volume; the anodic oxidation treatment is carried out at a temperature of 10℃–70℃, a voltage of 20V–50V, and a time of 1h–5h;
[0012] Step 5, Post-processing: The metal porous micro-nano composite liquid absorbing core blank obtained in Step 4 is cleaned with deionized water and anhydrous ethanol in sequence, and then heat-treated at 80℃~500℃ to obtain the metal porous micro-nano composite liquid absorbing core.
[0013] In step five of this invention, heat treatment is used to remove organic matter and moisture introduced during the preparation process.
[0014] The above method is characterized in that the metal powder in step one is selected from nickel powder, Inconel 625 powder, Inconel 718 powder, and 316L powder.
[0015] The method described above is characterized in that the particle size distribution range of the metal powder in step one is selected from: 80μm~180μm, 80μm~280μm, 300μm~400μm, -22μm, -16μm.
[0016] The above method is characterized in that the metal powder in step one is selected from nickel powder, Inconel 625 powder, and Inconel 718 powder, and the sintering atmosphere in step two is a hydrogen atmosphere with a hydrogen flow rate of 0.25 m³ / h. 3 / h~0.4m 3 / h. In this invention, nickel or nickel alloy powder is sintered in a hydrogen atmosphere, which ensures the sintering effect. At the same time, some of the nickel or nickel alloy powder is reduced during the sintering process, thereby improving its sintering activity.
[0017] The above method is characterized in that the metal powder in step one is selected from 316L powder, and the sintering in step two is carried out under vacuum conditions, with a vacuum degree not exceeding 9.0 × 10⁻⁶. -2 Pa. In this invention, 316L powder is vacuum sintered. The vacuum environment not only helps to remove the gas adsorbed on the surface of the 316L powder, but also avoids the adverse effects of impurities such as hydrogen on the properties of the resulting porous metal matrix.
[0018] Compared with the prior art, the present invention has the following advantages:
[0019] 1. This invention obtains a metal porous micro-nano composite liquid wick by setting micro-protrusion structures on the surface of a porous metal substrate and setting nano-porous structures on the micro-protrusion structures. The micro-nano structures effectively increase the surface area of the composite liquid wick, making it have higher heat transfer efficiency and stability compared to a single-pore unit liquid wick.
[0020] 2. The composite wick with micro-nano scale pore structure of the present invention has good capillary suction force for liquid working fluid, and has low flow resistance and high permeability, thereby effectively balancing the contradiction between capillary force and permeability of porous wick and thus improving the heat transfer capacity of heat pipe.
[0021] 3. This invention combines powder metallurgy, micro-milling and anodizing processes to develop a simple and controllable micro-nano composite metal porous liquid wicking method, which has important application prospects in the fields of high heat flux density, high power heat dissipation and thermal management of aerospace equipment.
[0022] 4. The metal porous micro-nano composite liquid wick prepared by this invention has the advantages of low cost and easy operation, and can be used as a metal functional material in the fields of heat exchange, direct alcohol fuel cells and the like.
[0023] The technical solution of the present invention will be further described in detail below with reference to the accompanying drawings and embodiments. Attached Figure Description
[0024] Figure 1 The images show the physical specimen and SEM image of the porous metal micro / nano composite liquid absorption core prepared in Example 1 of this invention. Detailed Implementation
[0025] Example 1
[0026] The preparation method of this embodiment includes the following steps:
[0027] Step 1: Pressing and molding of porous metal matrix: After loading 500g of nickel powder with a particle size distribution range of -22μm into the mold, it is placed in a cold isostatic pressing equipment for cold isostatic pressing and molding. The pressure is 160MPa and the holding time is 20s to obtain a nickel porous matrix green body.
[0028] Step 2: Sintering of the porous metal matrix: The nickel porous matrix green body obtained in Step 1 is sintered under a hydrogen atmosphere with a hydrogen flow rate of 0.3 m³ / s. 3 / h, the sintering temperature is 950℃, the holding time is 2h, and a nickel porous matrix is obtained;
[0029] Step 3: Machining of the micro-protrusion structure: The machining model of the micro-protrusion structure is designed using CAXA software. Then, the nickel porous substrate obtained in Step 2 is micro-milled using the designed machining model to form the micro-protrusion structure, resulting in a nickel porous substrate with a micro-protrusion structure on the surface. The feed rate for the micro-milling is 0.015 mm, and the rotation speed is 10000 rpm.
[0030] Step 4: Surface nano-sizing treatment of the micro-protrusion structure: The nickel porous substrate with micro-protrusion structure obtained in Step 3 is placed as the anode in an electrolytic cell containing ethylene glycol electrolyte, and a platinum sheet is used as the cathode. Anodizing treatment is performed at a temperature of 30°C, a voltage of 30V, and a time of 2 hours to form a nanoporous structure on the micro-protrusion structure, thus obtaining a nickel porous micro / nano composite liquid absorbent core blank; the ethylene glycol electrolyte contains 0.75% ammonium fluoride by mass and 2% H2O by volume.
[0031] Step 5, Post-processing: The nickel porous micro-nano composite liquid absorbing core blank obtained in Step 4 is cleaned with deionized water and anhydrous ethanol in sequence, and then heat-treated at 200℃ to obtain the nickel porous micro-nano composite liquid absorbing core.
[0032] like Figure 1 As shown, the nickel porous micro / nano composite liquid absorbent core prepared in this embodiment includes a nickel porous substrate, a micro-protrusion structure disposed on the surface of the nickel porous substrate, and a nanoporous structure on the micro-protrusion structure. Testing revealed that the porosity of the nickel porous substrate in this nickel porous micro / nano composite liquid absorbent core is 15%, the maximum pore size is 5 μm, and the thickness is 5 mm. The height, length, and width of the micro-protrusion structure on the surface of the nickel porous substrate are 0.5 mm, 0.5 mm, and 0.5 mm, respectively. The thickness of the nanoporous structure on the micro-protrusion structure is 5 μm, and the pore size is 30 nm to 75 nm.
[0033] Example 2
[0034] The difference between this embodiment and Embodiment 1 is that the particle size distribution range of the nickel powder in step one is -16μm.
[0035] Example 3
[0036] The preparation method of this embodiment includes the following steps:
[0037] Step 1: Pressing and molding of porous metal matrix: 500g of Inconel 718 powder with a particle size distribution range of 300μm~400μm is loaded into the mold and placed in a cold isostatic pressing equipment for cold isostatic pressing and molding. The pressure is 180MPa and the holding time is 25s to obtain the Inconel 718 porous matrix green body.
[0038] Step 2: Sintering of the porous metal matrix: The Inconel 718 porous matrix green body obtained in Step 1 is sintered under a hydrogen atmosphere with a hydrogen flow rate of 0.4 m³ / s. 3 The sintering temperature was 1100℃ and the holding time was 2.5h, resulting in an Inconel 718 porous matrix.
[0039] Step 3: Machining of the micro-boob structure: The machining model of the micro-boob structure is designed using CAXA software. Then, the Inconel718 porous substrate obtained in Step 2 is micro-milled using the designed machining model to form the micro-boob structure, resulting in an Inconel718 porous substrate with a micro-boob structure on its surface. The feed rate for the micro-milling is 0.015 mm, and the rotation speed is 10000 rpm.
[0040] Step 4: Surface nanostructuring of the micro-protrusion structure: The Inconel 718 porous substrate with micro-protrusion structure obtained in Step 3 is placed as the anode in an electrolytic cell containing ethylene glycol electrolyte, and a platinum sheet is used as the cathode. Anodizing is performed at a temperature of 30°C, a voltage of 30V, and a time of 3 hours to form a nanoporous structure on the micro-protrusion structure, resulting in an Inconel 718 porous micro-nano composite liquid absorbent core blank; the ethylene glycol electrolyte contains 0.75% ammonium fluoride by mass and 1.5% H2O by volume.
[0041] Step 5, Post-processing: The Inconel718 porous micro-nano composite liquid absorption core blank obtained in Step 4 is cleaned with deionized water and anhydrous ethanol in sequence, and then heat-treated at 200℃ to obtain the Inconel718 porous micro-nano composite liquid absorption core.
[0042] The Inconel718 porous micro / nano composite liquid absorbent core prepared in this embodiment includes an Inconel718 porous substrate, micro-protrusion structures disposed on the surface of the Inconel718 porous substrate, and nanoporous structures on the micro-protrusion structures. Testing revealed that the porosity of the Inconel718 porous substrate in this Inconel718 porous micro / nano composite liquid absorbent core is 35%, the maximum pore size is 10 μm, and the thickness is 3 mm. The height, length, and width of the micro-protrusion structures on the surface of the Inconel718 porous substrate are 0.5 mm, 0.5 mm, and 0.5 mm, respectively. The thickness of the nanoporous structures on the micro-protrusion structures is 15 μm, and the pore size is 30 nm to 95 nm.
[0043] Example 4
[0044] The preparation method of this embodiment includes the following steps:
[0045] Step 1: Pressing and molding of porous metal matrix: 500g of 316L powder with a particle size distribution range of 80μm~180μm is loaded into the mold and then placed in a cold isostatic pressing equipment for cold isostatic pressing and molding. The pressure is 160MPa and the holding time is 20s to obtain a 316L porous matrix green body.
[0046] Step 2: Sintering of the porous metal matrix: The 316L porous matrix green body obtained in Step 1 is sintered under vacuum conditions, with a vacuum degree not exceeding 9.0 × 10⁻⁶. -2 Pa, sintering temperature is 1250℃, holding time is 3.5h, to obtain 316L porous matrix;
[0047] Step 3: Machining of the micro-boob structure: The machining model of the micro-boob structure is designed using CAXA software. Then, the 316L porous substrate obtained in Step 2 is micro-milled using the designed machining model to form the micro-boob structure, resulting in a 316L porous substrate with a micro-boob structure on its surface. The feed rate for the micro-milling is 0.01 mm, and the rotation speed is 8000 rpm.
[0048] Step 4: Surface nano-sizing treatment of the micro-protrusion structure: The 316L porous substrate with micro-protrusion structure obtained in Step 3 is placed as the anode in an electrolytic cell containing ethylene glycol electrolyte, and a platinum sheet is used as the cathode. Anodizing treatment is performed at a temperature of 10℃, a voltage of 20V, and a time of 1h to form a nanoporous structure on the micro-protrusion structure, resulting in a 316L porous micro-nano composite liquid absorbent core blank; the ethylene glycol electrolyte contains 0.25% ammonium fluoride by mass and 1% H2O by volume.
[0049] Step 5, Post-processing: The 316L porous micro-nano composite liquid absorption core blank obtained in Step 4 is cleaned with deionized water and anhydrous ethanol in sequence, and then heat-treated at 80℃ to obtain the 316L porous micro-nano composite liquid absorption core.
[0050] The 316L porous micro / nano composite liquid absorbent core prepared in this embodiment includes a 316L porous substrate, a micro-protrusion structure disposed on the surface of the 316L porous substrate, and a nanoporous structure on the micro-protrusion structure. Testing revealed that the porosity of the 316L porous substrate in this 316L porous micro / nano composite liquid absorbent core is 33%, the maximum pore size is 25 μm, and the thickness is 5 mm. The height, length, and width of the micro-protrusion structure on the surface of the 316L porous substrate are 0.3 mm, 0.3 mm, and 0.3 mm, respectively. The thickness of the nanoporous structure on the micro-protrusion structure is 5 μm, and the pore size is 30 nm to 95 nm.
[0051] Example 5
[0052] The preparation method of this embodiment includes the following steps:
[0053] Step 1: Pressing and molding of porous metal matrix: 500g of Inconel 625 powder with a particle size distribution range of 80μm~180μm is loaded into the mold and then placed in a cold isostatic pressing equipment for cold isostatic pressing and molding. The pressure is 200MPa and the holding time is 20s to obtain the Inconel 625 porous matrix green body.
[0054] Step 2: Sintering of the porous metal matrix: The Inconel 625 porous matrix green body obtained in Step 1 is sintered in a hydrogen atmosphere with a hydrogen flow rate of 0.25 m³ / h. 3 The sintering temperature was 1200℃ and the holding time was 3.5h, resulting in an Inconel 625 porous matrix.
[0055] Step 3: Machining of the micro-boob structure: The machining model of the micro-boob structure is designed using CAXA software. Then, the Inconel625 porous substrate obtained in Step 2 is micro-milled using the designed machining model to form the micro-boob structure, resulting in an Inconel625 porous substrate with a micro-boob structure on its surface. The feed rate for the micro-milling is 0.02 mm, and the rotation speed is 12000 rpm.
[0056] Step 4: Surface nanostructuring of the micro-protrusion structure: The Inconel 625 porous substrate with micro-protrusion structure obtained in Step 3 is placed as the anode in an electrolytic cell containing ethylene glycol electrolyte, and a platinum sheet is used as the cathode. Anodizing is performed at 70°C, 50V, for 1 hour to form a nanoporous structure on the micro-protrusion structure, resulting in an Inconel 625 porous micro / nano composite absorbent core blank. The ethylene glycol electrolyte contains 1.25% ammonium fluoride by mass and 2% H2O by volume.
[0057] Step 5, Post-processing: The Inconel 625 porous micro-nano composite liquid absorbing core blank obtained in Step 4 is cleaned with deionized water and anhydrous ethanol in sequence, and then heat-treated at 500℃ for 1 hour to obtain the Inconel 625 porous micro-nano composite liquid absorbing core.
[0058] The Inconel 625 porous micro / nano composite liquid absorbent core prepared in this embodiment includes an Inconel 625 porous substrate, micro-protrusion structures disposed on the surface of the Inconel 625 porous substrate, and nanoporous structures on the micro-protrusion structures. Testing revealed that the Inconel 625 porous substrate in this Inconel 625 porous micro / nano composite liquid absorbent core has a porosity of 45%, a maximum pore size of 15 μm, and a thickness of 10 mm. The micro-protrusion structures on the surface of the Inconel 625 porous substrate have a height of 0.1 mm, a length of 0.7 mm, and a width of 0.7 mm. The nanoporous structures on the micro-protrusion structures have a thickness of 30 μm and a pore size of 30 nm to 95 nm.
[0059] Example 6
[0060] The preparation method of this embodiment includes the following steps:
[0061] Step 1: Pressing and molding of porous metal matrix: 500g of nickel powder with a particle size distribution range of 80μm~280μm is loaded into the mold and then placed in a cold isostatic pressing equipment for cold isostatic pressing and molding. The pressure is 160MPa and the holding time is 30s to obtain a nickel porous matrix green body.
[0062] Step 2: Sintering of the porous metal matrix: The nickel porous matrix green body obtained in Step 1 is sintered under a hydrogen atmosphere with a hydrogen flow rate of 0.3 m³ / s. 3 The sintering temperature was 1150℃ and the holding time was 1.5h, resulting in a nickel porous matrix;
[0063] Step 3: Machining of the micro-protrusion structure: The machining model of the micro-protrusion structure is designed using CAXA software. Then, the nickel porous substrate obtained in Step 2 is micro-milled using the designed machining model to form the micro-protrusion structure, resulting in a nickel porous substrate with a micro-protrusion structure on the surface. The feed rate for the micro-milling is 0.015 mm, and the rotation speed is 10000 rpm.
[0064] Step 4: Surface nano-sizing treatment of the micro-protrusion structure: The nickel porous substrate with micro-protrusion structure obtained in Step 3 is placed as the anode in an electrolytic cell containing ethylene glycol electrolyte, and a platinum sheet is used as the cathode. Anodizing treatment is performed at a temperature of 30°C, a voltage of 50V, and a time of 1 hour to form a nanoporous structure on the micro-protrusion structure, thus obtaining a nickel porous micro / nano composite liquid absorbent core blank; the ethylene glycol electrolyte contains 0.75% ammonium fluoride by mass and 2% H2O by volume.
[0065] Step 5, Post-processing: The nickel porous micro-nano composite liquid absorbing core blank obtained in Step 4 is cleaned with deionized water and anhydrous ethanol in sequence, and then heat-treated at 200℃ to obtain the nickel porous micro-nano composite liquid absorbing core.
[0066] The nickel porous micro / nano composite liquid absorbent core prepared in this embodiment includes a nickel porous substrate, a micro-protrusion structure disposed on the surface of the nickel porous substrate, and a nanoporous structure on the micro-protrusion structure. Testing revealed that the porosity of the nickel porous substrate in this nickel porous micro / nano composite liquid absorbent core is 35%, the maximum pore size is 15 μm, and the thickness is 5 mm. The height, length, and width of the micro-protrusion structure on the surface of the nickel porous substrate are 0.5 mm, 0.5 mm, and 0.5 mm, respectively. The thickness of the nanoporous structure on the micro-protrusion structure is 5 μm, and the pore size is 50 nm to 95 nm.
[0067] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention in any way. Any simple modifications, alterations, and equivalent changes made to the above embodiments based on the inventive essence shall still fall within the protection scope of the present invention.
Claims
1. A porous metal micro / nano composite liquid-absorbing core, characterized in that, The invention includes a porous metal substrate, micro-protrusion structures disposed on the surface of the porous metal substrate, and nanoporous structures on the micro-protrusion structures. The porous metal substrate has a porosity of 15% to 45%, a maximum pore size of 5 μm to 25 μm, and a thickness of 1 mm to 10 mm. The micro-protrusion structures have a thickness of 0.1 mm to 0.5 mm, a length of 0.3 mm to 0.7 mm, and a width of 0.3 mm to 0.7 mm. The nanoporous structures are prepared by anodizing and have a thickness of 5 μm to 30 μm and a pore size of 30 nm to 95 nm.
2. A method for preparing the metal porous micro / nano composite liquid-absorbing core as described in claim 1, characterized in that, The method includes the following steps: Step 1: Pressing and forming of porous metal matrix: After loading the metal powder into the mold, it is placed in a cold isostatic pressing equipment for cold isostatic pressing and forming to obtain a green metal porous matrix; the pressure of the cold isostatic pressing is 160MPa~200MPa, and the holding time is 20s~30s. Step 2: Sintering of the porous metal matrix: The porous metal matrix green body obtained in Step 1 is sintered to obtain a porous metal matrix; the sintering temperature is 950℃~1250℃, and the holding time is 1.5h~3.5h. Step 3: Machining of the micro-boob structure: The machining model of the micro-boob structure is designed using CAXA software. Then, the designed machining model is used to perform micro-milling on the porous metal substrate obtained in Step 2 to form the micro-boob structure, resulting in a porous metal substrate with a micro-boob structure on its surface. The feed rate used in the micro-milling is 0.01mm~0.02mm, and the rotation speed is 8000rpm~12000rpm. Step 4: Surface nanostructuring of the micro-protrusion structure: The porous metal substrate with micro-protrusion structure obtained in Step 3 is placed as the anode in an electrolytic cell containing ethylene glycol electrolyte, and a platinum sheet is used as the cathode for anodic oxidation treatment to form a nanoporous structure on the micro-protrusion structure, resulting in a porous metal micro / nano composite liquid absorbent core blank; the ethylene glycol electrolyte contains 0.25%~1.25% ammonium fluoride by mass and 1%~2% H2O by volume; the anodic oxidation treatment is carried out at a temperature of 10℃~70℃, a voltage of 20V~50V, and a time of 1h~5h; Step 5, Post-processing: The metal porous micro-nano composite liquid absorbing core blank obtained in Step 4 is cleaned with deionized water and anhydrous ethanol in sequence, and then heat-treated at 80℃~500℃ to obtain the metal porous micro-nano composite liquid absorbing core.
3. The method according to claim 2, characterized in that, The metal powder mentioned in step one is selected from nickel powder, Inconel 625 powder, Inconel 718 powder, and 316L powder.
4. The method according to claim 2, characterized in that, The particle size distribution range of the metal powder mentioned in step one is selected from: 80μm~180μm, 80μm~280μm, 300μm~400μm, -22μm, -16μm.
5. The method according to claim 3, characterized in that, The metal powder mentioned in step one is selected from nickel powder, Inconel 625 powder, and Inconel 718 powder. The sintering atmosphere mentioned in step two is a hydrogen atmosphere, and the hydrogen flow rate is 0.25 m³ / h. 3 / h~0.4m 3 / h.
6. The method according to claim 3, characterized in that, The metal powder mentioned in step one is selected from 316L powder, and the sintering in step two is carried out under vacuum conditions, with a vacuum degree not exceeding 9.0 × 10⁻⁶. -2 Pa.
Citation Information
Patent Citations
Manufacturing method of composite porous structure wick
CN114888304A
Method and equipment for quantum vacuum energy extraction
WO2013071100A1